An insight into neutral layer shifting in tube bending. (March 2018) - Li, H.; Ma, J.; Liu, B.Y.; Gu, R.J.; Li, G.J.
Abstract: Neutral layer shifting (NLS) is the most fundamental phenomenon during tube bending, which characterizes tension-compression (T-C) non-uniform bending deformation and directly affects multi-defect constrained formability and bending limits. However, the essentials of NLS in tube bending have not yet been clarified, viz., why does the neutral layer (NL) generally shift inward, can the NL shift outward possibly and even can be positively reconstructed? To address these issues, via analyzing the equilibrium conditions of moment and force during tube bending, an axial force equilibrium (AFE)-based hybrid analytical-numerical framework for NLS calculation is established and numerically implemented, in which the tubular materials properties such as the anisotropy/asymmetry behaviors, and the geometry parameters such as bending radius, tube diameters and wall thickness can be comprehensively considered. Taking rotary draw bending of Ti-3Al-2.5 V tube and press bending of AZ31 and A6063 tubes as the cases, the above NLS model is fully evaluated and validated. Using the above platform, the NLS rules related to the geometrical parameters and intrinsic material parameters are quantitatively identified, and within the above framework combined with the experiments, a thorough insight into the NLS upon tube bending is thus presented, viz., given geometrical parameters of bending, under combined action of the evolution of material properties and multi-tool induced additional forces, the inevitable transient T-C non-uniform deformation can be positively coordinated to satisfy the equilibrium of force, then the NLS can be reconstructed to propose innovative processes for improving bending formability. Highlights: A thorough insight into NLS essentials in tube bending is presented from point of materials properties, geometries and processing operations. A hybrid analytical-numerical framework for NLS calculation in tube bending is established, numerically implemented and fully evaluated. The intrinsic properties such as anisotropy/asymmetry, hardening behaviors, and geometries can be fully considered in the NLS framework. The NLS rules related to the geometrical parameters and intrinsic material parameters are quantitatively identified and clarified. NLS can be reconstructed by positively coordinating T-C non-uniform deformation for innovative process design with improved formability.